2016
DOI: 10.1002/ps.4272
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the availability of food to control feral pigeons: changes in population size and composition

Abstract: Results show the effectiveness of public information to manage feral pigeon populations in a large city, and that control operations can exert important selection pressure on the population, leading to changes in population composition. © 2016 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
18
0
4

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(30 citation statements)
references
References 20 publications
(41 reference statements)
0
18
0
4
Order By: Relevance
“…Silva and Medeiros (2008) indicate that humans are increasingly concerned about pigeon populations (and presumably their accumulated faeces) in the urban space, and in response (Senar et al 2017), demonstrate that food control is key to population reduction. A greater understanding of the chemical responses of urban spaces to faeces, both recently voided and accumulated, is necessary to complete the picture of the effects of feral pigeons.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Silva and Medeiros (2008) indicate that humans are increasingly concerned about pigeon populations (and presumably their accumulated faeces) in the urban space, and in response (Senar et al 2017), demonstrate that food control is key to population reduction. A greater understanding of the chemical responses of urban spaces to faeces, both recently voided and accumulated, is necessary to complete the picture of the effects of feral pigeons.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, studies have shown that population densities are higher in the city centres than at the periphery (Uribe et al 1984) or in suburbia (Ferman et al 2010), with the nature of micro-habitat as one of the determinants (Przybylska et al 2012). The density of feral pigeon populations in an urban community appears to be directly related to the amount of available food (intentional feeding, spillage, organic waste) (Sol et al 2000;Buijs & Van Wijnen 2001;Morand-Ferron et al 2009;Przybylska et al 2012;Senar et al 2017) which is also related to the size of human population (Hetmański et al 2011). A large quantity of energy requirements of the feral pigeons is provided by edible waste in public areas (Jokimaki & Suhonen 1998;Buijs & Van Wijnen 2001).…”
Section: Urban Pigeonsmentioning
confidence: 99%
See 1 more Smart Citation
“…, Senar et al. ). To maintain avian biodiversity, being able to predict which species will struggle or persist in human‐impacted environments will help focus conservation efforts (see Sih for a conceptual overview of behavioral changes in response to HIREC).…”
mentioning
confidence: 99%
“…Feral pigeons ( Columba livia ) are an important risk for human health, and a nuisance in building conservation in many cities. Senar et al showed how educating the public on reducing the food availability to birds resulted in a 40% reduction in the population size of pigeons . The common myna ( Acridotheres tristis ) is a serious threat to the conservation of native endemic avifauna in many islands.…”
mentioning
confidence: 99%